2021
DOI: 10.1002/14651858.cd013668.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions for self-harm in adults

Abstract: Analysis 2.2. Comparison 2 Interventions for multiple repetition of self-harm (SH)/probable personality disorder vs treatment as usual (TAU) or other alternative forms of psychotherapy, Outcome 2 Repetition of SH at 6 months. Analysis 2.3. Comparison 2 Interventions for multiple repetition of self-harm (SH)/probable personality disorder vs treatment as usual (TAU) or other alternative forms of psychotherapy, Outcome 3 Repetition of SH at 12 months. Analysis 2.4. Comparison 2 Interventions for multiple repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 364 publications
2
51
0
8
Order By: Relevance
“…In addition to mental health care to treat underlying psychiatric conditions, psychosocial interventions that directly target suicidal thoughts and behaviour should be made available to prisoners in need ( Meerwijk et al, 2016 ). Current evidence, however, largely relies on either small and uncontrolled prison studies ( Winicov, 2019 ) or trials conducted within community settings ( Fox et al, 2020 ; Witt et al, 2021 ), although recent randomised controlled trials found encouraging results that cognitive behavioural therapy ( Pratt et al, 2015 ) and psychodynamic interpersonal therapy ( Walker et al, 2017 ) may improve outcomes in suicidal prisoners. Because this work is still only at the piloting stages, further adequately powered trials are required to evaluate their effectiveness in prisons.…”
Section: Preventionmentioning
confidence: 99%
“…In addition to mental health care to treat underlying psychiatric conditions, psychosocial interventions that directly target suicidal thoughts and behaviour should be made available to prisoners in need ( Meerwijk et al, 2016 ). Current evidence, however, largely relies on either small and uncontrolled prison studies ( Winicov, 2019 ) or trials conducted within community settings ( Fox et al, 2020 ; Witt et al, 2021 ), although recent randomised controlled trials found encouraging results that cognitive behavioural therapy ( Pratt et al, 2015 ) and psychodynamic interpersonal therapy ( Walker et al, 2017 ) may improve outcomes in suicidal prisoners. Because this work is still only at the piloting stages, further adequately powered trials are required to evaluate their effectiveness in prisons.…”
Section: Preventionmentioning
confidence: 99%
“…Trotz aller berechtigten Kritik scheint die suizidfokussierte Psychotherapie die derzeit aussichtsreichste Kandidatin unter den individuumszentrierten Interventionen zu sein: Mit Ausnahme von Lithium [44] konnte bislang für kein Medikament eine stabile antisuizidale Wirkung nachgewiesen werden [23] und andere somatische Behandlungsverfahren (Elektrokrampftherapie, Schlafentzug) wurden zu selten untersucht, um eine Einschätzung vornehmen zu können. Vor dem Hintergrund der Ergebnisse der Cochrane-Reviews von Witt und Kolleg*innen [6,7] empfehlen sich insbesondere KVT, DBT und MBT für weitere Wirksamkeitsstudien. Weitere Details zur Lizenz entnehmen Sie bitte der Lizenzinformation auf http://creativecommons.org/ licenses/by/4.0/deed.de.…”
Section: Diskussionunclassified
“…Im Rahmen von 2 aktuellen Cochrane-Reviews haben Witt et al. [ 6 , 7 ] Studien zur Effektivität psychosozialer Interventionen bei der Behandlung von Erwachsenen und von Kindern/Jugendlichen zusammengefasst. Einbezogen in die Metaanalysen wurden ausschließlich randomisiert kontrollierte Studien, in denen eine psychosoziale Intervention mit einer Vergleichsbedingung (zumeist Regelversorgung, engl.…”
Section: Evidenzen Aus Systematischen Reviews Und Metaanalysenunclassified
See 2 more Smart Citations